Early stopping of randomized clinical trials for overt efficacy is problematic. - Bassler, D; Montori, V; Briel, M; Glasziou, P; Guyatt, G (2008)
OBJECTIVE: To illustrate controversial issues associated with stopping randomized controlled trials (RCTs) early for apparent benefit. STUDY DESIGN AND SETTING: The article presents our review of prior relevant work and our research group's reflections on early stopping. RESULTS: Compelling evidence suggests that trials stopped early for benefit systematically overestimate treatment effects, sometimes by a large amount. Unresolved controversies in trials stopped early for benefit include ethical and statistical problems in the interpretation of results. CONCLUSIONS: The best strategy to minimize the problems associated with early stopping of RCTs for benefit is not to stop early. As an alternative, we suggest a threefold approach: a low P-value as the threshold for stopping at the time of interim analyses, not to look before a sufficiently large number of events has accrued and continuation of enrollment and follow-up for a further period.